Multi-model based pressure optimization for large-scale water distribution networks. (February 2020) - Zhang, Yuan; Li, Shaoyuan; Zheng, Yi; Zou, Yuanyuan
Abstract: In the operation of urban water distribution networks (WDNs), the supply pressure to users should be kept low while meeting the lower bound to satisfy users' water demand, reduce leakages and power consumption. In this paper, a multi-model based pressure optimization method for large-scale WDNs is proposed, where the pressure of the whole WDNs is represented by the pressure of key nodes and key pump station nodes based on the calculation of pressure transfer relationship and a developed network simplification method, the multiple linear models are constructed to approximate the pressure transfer relationships, and the models between the selected key nodes and key pump station nodes are used for the pressure optimization of the whole WDNs. The proposed methods are operation data based, which overcomes the difficulty in constructing accurate and complicated hydraulic models for large-scale WDNs. The network simplification reduces data requirements in multiple model construction and ensures real-time control. In the simulation case, which is part of Shanghai's WDNs, the supply pressure to users is optimized to lower and more homogeneous value without violating the lower bound by applying the proposed approach, which is significant in reducing water leakages and energy consumption.